Danish and British popular Euroscepticism compared: A sceptical assessment of the concept - Catharina Sørensen (Danish Institute for International Studies (DIIS), 2004)
The aim of the working paper is to examine similarities and differences between Danish and British sceptical or negative public attitudes towards the European Union. It looks at problems involved with defining and measuring the phenomenon of popular euroscepticism, before turning to characteristics specific for the case countries. The conclusion drawn from the comparison is that the phenomenon differs significantly even between two countries often associated for a discernible euroscepticism. In conclusion, the contemporary relevance of the study of popular euroscepticism is discussed with reference to the increasing use of referenda as a means to settle political questions in today's EU.
Keywords: 330; Vergleich; Dänemark; Großbritannien; Europapolitik; Meinung